2016
DOI: 10.1063/1.4949615
|View full text |Cite
|
Sign up to set email alerts
|

The life times of polymer composites in construction

Abstract: This paper discusses examples that prove the long-term reliability of Fiber Reinforced Polymers (FRP) under extreme loading conditions and outdoor weathering. Results of polymer/steel-composite anchorage systems, Glass Fiber Reinforced Polymer (GFRP) plates and shells, GFRP box girders, Carbon Fiber Reinforced Polymer (CFRP) posttensioning tendons and CFRP stays are going to be presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
(6 reference statements)
0
2
0
Order By: Relevance
“…The examples described in this paper prove that FRPs and polymers are very reliable construction materials, if correctly applied (see also [37] If FRPs are exposed to direct UV, there will be a gradual degradation of the polymer matrix at the surface. From a structural point of view this is no problem but it looks ugly.…”
Section: Recommendationsmentioning
confidence: 59%
“…The examples described in this paper prove that FRPs and polymers are very reliable construction materials, if correctly applied (see also [37] If FRPs are exposed to direct UV, there will be a gradual degradation of the polymer matrix at the surface. From a structural point of view this is no problem but it looks ugly.…”
Section: Recommendationsmentioning
confidence: 59%
“…As an advanced nonmetallic material, carbon-fiber-reinforced polymer (CFRP) has been considered the ideal material for replacing steel cables since 1982 [2]. Regarding their lifetime and mechanical properties, carbon-fiber composites have the highest potential for replacing steel cables, compared to aramid, glass, or basalt, because of their high strength, light weight, no corrosion risk, excellent creep and fatigue resistance, low linear expansion coefficient, and relaxation [3][4][5][6]. Existing studies have indicated that the application of CFRP could effectively solve the problems of corrosion, fatigue, self-weight, and prestress loss in the application of steel cables and could improve the overall performance of cable structures [7][8][9].…”
Section: Introductionmentioning
confidence: 99%